Pathological staging of chorioamnionitis contributes to complications in preterm infants - Jiayu Miao; Zhuxiao Ren; Yunbei Rao; Xin Xia; Jianlan Wang; Fang Xu; Xiaoling Zhang; Jie Yang (Italian Journal of Pediatrics, 2020)
Abstract Objective To investigate the effect of pathological staging of chorioamnionitis (CA) on complications in preterm infants; Methods A single-center, retrospective study was conducted to choose singleton preterm infants (gestational age < 37 weeks) from the Department of Obstetrics and Gynecology in our hospital from December 2016 to December 2017. The basic data and placental pathological results were retrospectively collected. According to the placental pathological results of whether inflammation infiltrating amnion, CA 0/I phase was classified into non-amnionitis group, CA II/III phase was classified into amnionitis group, the incidence of common complications in preterm infants was compared. Further, logistic regression was used to analyze the effects of amnionitis on complications after being adjusted to gestational age, birth weight and thrombocytopenia. Results A total of 221 preterm infants were enrolled, including 186 cases in non-amnionitis group and 35 cases in amnionitis group. The gestational age of amnionitis group (32.00 ± 2.71 weeks) was significantly lower than non-amnionitis group (34.14 ± 2.06 weeks), birth weight (1.93 ± 0.64 kg) was significantly lower than that of non-amnionitis group (2.26 ± 0.58 kg), and the hospital stay in amnionitis group was significantly longer (25.71 ± 19.23 days), all of the difference above was statistically significant(P < 0.05). The incidence of intraventricular hemorrhage (IVH) in amnionitis group (37.14%) was significantly higher than that in non-amnionitis group (13.98%) (P = 0.002), and the risk of IVH was significantly increased by amnionitis (OR = 3.636, 95%CI: 1.632–8.102); after correction of gestational age, birth weight and thrombocytopenia, the risk of IVH was still significantly increased (OR = 2.471, P = 0.046, 95% CI: 1.015–6.015). And the late-onset IVH was more common (P = 0.009). Conclusion Amnionitis leads to a significant reduction in gestational age and birth weight in preterm infants, and it is an independent risk factor for IVH.